(untitled) (Tempo e Argumento, 2023)
Olavo de Carvalho was one of the main representatives of the extreme right in Brazil, with several followers and having influenced members of the government of Jair Bolsonaro (1919-1922), using social networks, traditional media and Philosophy courses taught by him as means of disseminating his ideas. The ideologist built a conspiracy-based narrative about the New World Order, pointing to three groups called “globalists” – Russia and China; the financial elites of the West; and the group The Islamic Fraternity -, which would act together, in spite of different projects of domination, against the Judeo-Christian civilization and the “true American nation”, the great representative of Western values. The article aims to critically analyze the Olavist narrative, also conducting a conceptual discussion on the terms Extreme Right and Traditionalism, in order to contribute to the understanding of the nature of Carvalho’s thought. Taking into account that the author lived in the USA, the work also stands that his speech expresses a petty-bourgeois and representative worldview of the dissatisfaction of a white and Christian middle level of North American society, which has been missing opportunities for economic insertion as a result of existing problems in the US economy, in the context of inter-imperialist competition with the Russian-Chinese bloc. Therefore, it is essential to point out the correlation of the Olavist narrative on the New World Order with the disputes in the field of current geopolitics, which places the USA in opposition to Russia and China in the configuration of the international order.